TRAIN CONFIDENCE IN SPEAKING ENGLISH BY USING A MIRROR - Atrianus Toni (Suluh Adiluhung Publisher (SAPub), 2025)
This study explores the effectiveness of using mirrors as a tool to boost learners’ confidence in speaking English. Confidence is a critical factor in mastering spoken language, as it enables learners to practice fluency, pronunciation, and expression without fear of judgment. The research employs a qualitative approach, analyzing the experiences of English learners who incorporate mirror practice into their study routines. Participants engage in structured activities, including self-introductions, storytelling, and impromptu speeches while observing their reflections. The mirror serves as a visual aid to build self-awareness and simulate the presence of an audience. Findings reveal that mirror practice enhances self-confidence, reduces anxiety, and fosters self-correction in pronunciation and body language. This simple yet effective method encourages consistent practice, leading to noticeable improvements in speaking skills. The study concludes that incorporating mirrors into language learning can significantly impact learners' confidence and oral communication proficiency, especially for self-directed learning environments.